A critical appraisal of evidence-and consensus-based guidelines for actinic keratosis - Wessely, Anja; Steeb, Theresa; Heppt, Franz; Hornung, Annkathrin; Kaufmann, Matthias; Koch, Elias; Toussaint, Frédéric; Erdmann, Michael; Berking, Carola; Heppt, Markus (Current Oncology, 2021)
Actinic keratoses (AK) are common lesions of the skin that can be effectively treated with several lesion-and field-directed treatments. Clinical practice guidelines assist physicians in choosing the appropriate treatment options for their patients. Here, we aimed to systematically identify and evaluate the methodological quality of currently available guidelines for AK. Guidelines published within the last 5 years were identified in a systematic search of guideline databases, Medline and Embase. Then, six independent reviewers evaluated the methodological quality using the tools “Appraisal of Guidelines for Research and Evaluation” (AGREE II) and “Recommendation EXcellence” (AGREE-REX). The Kruskal–Wallis (H) test was used to explore differences among subgroups and Spearman’s correlation to examine the relationship between individual domains. Three guidelines developed by consortia from Canada, Germany and the United Kingdom were eligible for the evaluation. The German guideline achieved the highest scores, fulfilling 65 to 92% of the criteria in AGREE II and 67 to 84% in AGREE-REX, whereas the Canadian guideline scored 31 to 71% of the criteria in AGREE II and 33 to 46% in AGREE-REX. The domains “stakeholder involvement“ and “values and preferences“ were identified as methodological weaknesses requiring particular attention and improvement in future guideline efforts.
CRIS-Team Scopus Importer:2021-04-02
Keywords: actinic keratosis; AGREE; Level of evidence; Practice guideline; Solar keratosis